Impact of static synchronous compensator STATCOM installation in power quality improvement - Ismail Moufid; Zineb En-nay; Soukaina Naciri; Hassan El Moussaoui; Tijani Lamhamdi; Hassane El Markhi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The present work investigates the flexible AC transmission system (FACTS) device's role to improve the voltage stability for a distribution network of various types of loads. Our analysis was based on using a static synchronous compensator (STATCOM) device over a test distribution system. Firstly, a detailed description of the mathematical model used in our system is presented. Then we studied the effect of inductive and capacitive loads with and without STATCOM. To investigate the efficacy and robustness of using STATCOM in a distribution network, a test system is developed using MATLAB/Simulink, where we analyzed the voltage profile in different cases. The results of the simulation demonstrate that the STATCOM plays a critical role in optimizing the voltage profiles of distribution systems, either capacitive or inductive.